Influence of the dietary intake of medium chain triglycerides on body composition, energy expenditure and satiety: a systematic review - A. C. Rego Costa (Nutrición Hospitalaria)
Increased prevalence of obesity is associated with the growth of chronic degenerative diseases. One of the main factors associated with this increase is the change in nutritional status of individuals. Medium chain triglycerides (MCT) are rapidly metabolized and less stored in the adipose tissue, being a possible tool for weight control. In order to analyze the influence of consumption of this lipid on satiety, body composition and energy expenditure (EE), a literature review was performed of controlled clinical studies reported in PUBMED and ELSEVIER between the years 2000 and 2010. Fourteen articles were selected presenting short and long-term intervention. Among these, six showed a decrease in body mass of individuals, with consequent loss of weight. Only one showed a positive effect on satiation and four showed an increase in EE. Thus the results are inconclusive and there is a need for further controlled studies with standardized amounts of MCT, so that its use can become an alternative for obesity nutritional treatment.